Understanding the Electoral Preferences of Beginner Voters in the 2020 Bulukumba Local Elections - Harsyaf, Nurul Fitriana; Khaerah, Nur (Journal of Contemporary Local Politics, 2023)
Law no. 10 of  2008 concerning general elections states that first-time voters are those who are voting for the first time and are 17 years old or more or are/have been married and have the right to vote in general elections (and the Regional Head Election). New voters who have just entered voting age also do not have a broad political reach to determine where they should vote. So, sometimes what they choose is not what they expected. The aim of the research is to find out the preferences of novice voters in the 2020 Bulukumba regional elections. The type of research used is qualitative with a case study approach. The informants in this research were six (6) people consisting of the Bulukumba KPUD, political parties and first-time voters. The results of the research regarding the Political Preferences of Beginner Voters in the 2020 Pilkada in Bulukumba Regency are: first, sociological, the condition of beginner voters who are still unstable and have minimal understanding of politics tends to make their political attitudes and direction of support follow the family and community in the voter's environment. Second, psychologically, the emotional closeness and image of the candidate to first-time voters makes new voters participate as volunteers in supporting the candidate through campaign activities using a social media approach and competition activities. Third, Rational, the level of education of novice voters is a determining factor in voters' attitudes in determining political attitudes, where only a few novice voters make their choices through program analysis and candidate profiles obtained from various information.